SOME WAYS OF MEASURING TEMPERATURE AND MODERN SENSORS - Горбачук, Микола; Хлєбнікова, Валерія (Modern engineering and innovative technologies, 2024)
Several methods of measuring temperature and sensors for these purposes are considered. The main characteristics and designs of the technical means used are given. The main attention is paid to semiconductor temperature sensors based on the thermistor eff